Manufacturing method for hydrogen fuel cell titanium metal bipolar plate substrate
The manufacturing method for hydrogen fuel cell titanium bipolar plates addresses poor molding performance and high costs by controlling impurity content and using EB smelting, resulting in high-purity substrates with improved forming performance and corrosion resistance, enhancing fuel cell reliability and lifespan.
Patent Information
- Application Number
- JP2023548997
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-08
- Filing Date
- 2022-09-07
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2042-09-07
AI Technical Summary
Conventional titanium base materials for hydrogen fuel cell bipolar plates suffer from poor molding performance, high production costs, and difficulty in processing, limiting their widespread use and application due to high impurity content and complex environmental conditions.
A manufacturing method involving EB smelting, controlled impurity content, multi-step rolling and annealing, and high-purity argon gas protection to produce a titanium metal bipolar plate substrate with precise thickness and surface quality, ensuring excellent forming performance and reduced production costs.
The method enhances the molding performance, reduces production costs, and improves the reliability and lifespan of hydrogen fuel cells by using high-purity titanium substrates with controlled impurity levels, ensuring high power density and corrosion resistance.
Smart Images

Figure 0007607858000007 
Figure 0007607858000008 
Figure 0007607858000009
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of non-ferrous metal processing, and in particular to a method for manufacturing hydrogen fuel cell titanium metal bipolar plate substrates. [Background technology]
[0002] Hydrogen fuel cells are a tool for efficient and clean utilization of hydrogen energy, and have the advantages of high energy conversion rate, low heat radiation, low noise, long duration, zero emission, etc., and can be widely applied to automobiles, ships, aerospace, and distributed power sources, and have broad application prospects. As the main components of hydrogen fuel cell stacks, bipolar plates play multiple functions such as current collection, conduction, heat dissipation, uniform distribution of reaction medium, and leakage prevention, and operate in complex and adverse environments with multi-field coupling such as humid, electrochemical corrosion, and acid corrosion. Once the bipolar plate substrate corrodes and leaks, it will cause the hydrogen fuel cell stack to be disabled and safety risks will be created, so the bipolar plate has a great impact on the performance, life, and reliability of the entire fuel cell.
[0003] At present, hydrogen fuel cell bipolar plates mainly include graphite bipolar plates and metal bipolar plates. Graphite bipolar plates have the disadvantages of being easily brittle, difficult to assemble, difficult to reduce thickness, and low machining efficiency, which makes the graphite bipolar plate hydrogen fuel cell have a large volume, low power density, and high cost, limiting the prospects for application in passenger cars and other fields. The material of the metal bipolar plate is mainly stainless steel, but stainless steel is prone to surface corrosion in the acidic environment of the hydrogen fuel cell, and the metal ions dissolved by corrosion are prone to catalyst poisoning, which makes the life and reliability of the hydrogen fuel cell relatively short. Titanium metal has the advantages of corrosion resistance, low density, etc., which contributes to improving the performance, life and reliability of the hydrogen fuel cell, and is a desirable material for the hydrogen fuel cell metal bipolar plate substrate.
[0004] The weight of the metal bipolar plate is more than 50% of the total weight of the stack, and the future market demand is very large. The thickness of the titanium metal bipolar plate substrate for hydrogen fuel cell is generally 0.05-0.2mm, the depth and groove width of the pressed microstructure channel are generally 0.2-2.0mm, the pressed projected area is more than 50% of the total area of the plate surface, and the surface coating process is required later. The forming performance, dimensional accuracy, and surface quality of the substrate are strictly required. However, the forming performance of the traditional titanium substrate is relatively low during production, which limits its popularization and application in hydrogen fuel cells. In addition, the traditional titanium substrate has high production costs and large processing difficulty due to the strict material selection, which further limits its popularization and application in hydrogen fuel cells. It is necessary to design the manufacturing process and comprehensive performance of the titanium substrate and manufacture the titanium substrate according to the post-processing and service requirements of the hydrogen fuel cell metal bipolar plate. Therefore, in order to meet the demand for the use of hydrogen fuel cells, it has become a sharp demand for the development of the industry to develop a high-quality, low-cost titanium metal bipolar plate substrate. Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention aims to provide a method for producing titanium metal bipolar plate substrates for hydrogen fuel cells, which can produce high quality, low cost titanium metal bipolar plate substrates and meet the demand for titanium metal substrates for hydrogen fuel cells. [Means for solving the problem]
[0006] The technical solution adopted in the present invention is a method for manufacturing a titanium metal bipolar plate substrate for a hydrogen fuel cell, which comprises the steps of (1) smelting and machining a titanium sponge to obtain a titanium slab, and 当 is defined as the mass percentage of the total content of impurity elements in the titanium slab, the mass percentages of the contents of Fe, C, N, and O impurity elements are defined as [Fe]%, [C]%, [N]%, and [O]%, respectively, and [O] 当 The formula is [O] 当= [O]% + 0.5 * [Fe]% + 0.7 * [C]% + 2.5 * [N]%, where [Fe]% ≤ 0.050%, [C]% ≤ 0.040%, [N]% ≤ 0.010%, [O]% ≤ 0.080%, [O] 当 (2) selecting a titanium slab having a titanium content of ≦0.120% and directly using it for rolling; and (3) hot rolling the titanium slab selected in step (1) to obtain a hot rolled titanium coil having a black surface, and then performing a surface treatment to obtain a hot rolled titanium coil having no oxide film or defects remaining on the surface. (3) performing multi-step cold rolling and intermediate product annealing on the hot-rolled titanium coil obtained in step (2) to obtain a master tape for final product rolling; (4) performing final product rolling on the master tape for final product rolling obtained in step (3) to obtain a titanium tape; and (5) performing final product heat treatment and straightening on the titanium tape obtained in step (4) by a continuous annealing method under the protection of argon gas to obtain the titanium metal bipolar plate substrate for hydrogen fuel cell.
[0007] Furthermore, in the step (1), the titanium sponge is a titanium sponge of grade 0 or higher.
[0008] Furthermore, in the step (1), the smelting is carried out once in an EB furnace.
[0009] Furthermore, in step (2), the surface treatment process is to carry out annealing once and shot peening pickling twice on the hot-rolled titanium coil in a black skin state through a continuous annealing shot peening pickling line, and then carry out polishing and shot peening pickling treatment.
[0010] Furthermore, in step (3), the intermediate product is annealed at a temperature of 600 to 850°C.
[0011] Furthermore, in step (4), the deformation amount in the rolling process is 50% to 65%, and the unit tension is 200 to 400 kg / mm 2The rolling speed is 50-150 m / min, and the rolling force is 200-400 tons.
[0012] Furthermore, in the step (5), the heat treatment temperature of the continuous annealing is 600 to 800° C., the heat retention time is 0.5 to 2.5 min, and the annealing tension is 0.5 to 2.5 KN.
[0013] Furthermore, in step (5), the argon gas has a purity of ≧99.99%.
[0014] Furthermore, in the step (5), the tension in the straightening is 500 to 1500 KN, and the tensile deformation rate in the straightening is 0.1% to 0.3%.
[0015] Furthermore, the hydrogen fuel cell titanium metal bipolar plate substrate obtained in step (5) has a thickness precision of ≦±0.003 mm, a waviness of ≦1.5 mm / m, and a yield strength (R P0.2 )≦260MPa, and elongation (A 50mm )≧30%, the grain size is 6-10, and the cupping value is ≧6.0 mm. Effect of the Invention
[0016] The advantageous effects of the present invention are as follows:
[0017] 1. In the application, the manufacturing method of the present invention adopts the content of a single impurity element and the content of a comprehensive impurity element to carry out double control, and ensures the forming performance of the titanium metal bipolar plate substrate. Since different elements have different influence strengths, [O] 当 By taking the amount of impurity elements as an index for comprehensively evaluating the impact of the content of impurity elements on the press forming performance, it is possible to ensure the production of a bipolar plate substrate with good forming performance, while at the same time loosening the upper limit of the content of a single impurity element, lowering the standard for material selection, and broadening the selection range of titanium sponge, which is favorable for obtaining a wide range of materials and reducing the production cost.
[0018] 2. When applied, the manufacturing method of the present invention can obtain the optimal grain size range of the final product by controlling the annealing temperature and time, improve the elongation of the material, and ensure that the grains are uniformly deformed during the pressing process. At the same time, a comprehensive control index consisting of components, grain size, yield strength, elongation and cupping value is designed for the forming properties of the metal bipolar plate, which further improves the forming performance of the titanium substrate and ensures the special micro-channel forming requirements of the metal bipolar plate.
[0019] 3. The manufacturing method of the present invention has high production efficiency and low cost when applied. On the one hand, by adopting EB smelting once, which has high vacuum, high superheat, good effect of removing high and low density mixture, and refining effect, the increase of impurity elements can be reduced, and the quality of titanium slabs can meet the quality control requirements. In addition, the slab production flow is shortened by more than 40% compared with the conventional 2-3 times VAR smelting, and the yield is improved by more than 5%. On the other hand, by adopting the high temperature short time annealing process method, the efficiency of annealing production is improved, the consumption of argon gas is reduced, and the cost of annealing the substrate is further reduced.
[0020] 4. When the manufacturing method of the present invention is applied, the titanium metal bipolar plate substrate has excellent surface quality, uniform quality and good stability. Meanwhile, this manufacturing method has a high smelting vacuum, a large degree of superheat, and a good effect of removing high and low density mixed materials, and the slabs are manufactured using an EB furnace with refining function, which can significantly reduce defects such as mixed and porous in the final ultra-thin tape coil caused by metallurgical quality problems. Meanwhile, in the manufacturing process of hot-rolled titanium coil, this manufacturing method adopts the method of two-time pickling, polishing and re-pickling, which not only ensures thorough removal of oxide film, but also removes small defects that are difficult to observe through mechanical polishing and multiple shot peening pickling chemical methods, thereby minimizing the remaining defects in the final product.
[0021] 5. When the manufacturing method of the present invention is applied, the final titanium coil product adopts argon gas high temperature short time annealing, and is protected with high purity argon gas, thereby reducing the annealing time and significantly improving the thickness of the oxide layer of the titanium coil, and greatly reducing the difficulty and cost of removing the oxide layer before coating the titanium metal bipolar plate later.
[0022] 6. The titanium metal bipolar plate substrate obtained by the manufacturing method of the present invention is advantageous in improving the performance, life, and reliability of hydrogen fuel cells. Meanwhile, the density of titanium material is more than 40% lower than that of stainless steel, so that the power density per unit mass of the battery can be significantly increased and the performance of the battery can be improved. In addition, titanium has excellent corrosion resistance, and compared with stainless steel metal bipolar plates, even if the coating of the titanium metal bipolar plate is partially peeled off in a humid environment and an acidic environment, the bipolar plate does not corrode and the membrane electrode catalyst is not poisoned by Fe ions, so that the life of the hydrogen fuel cell can be significantly extended. Meanwhile, a hydrogen fuel cell stack is composed of hundreds of bipolar plates and membrane electrodes, and once leakage of the bipolar plate or the waviness and thickness accuracy exceed the standard due to integration errors and stress action, the stack will be damaged. The titanium substrate obtained by the manufacturing method of the present invention has good molding performance and excellent waviness and thickness accuracy, and can significantly improve the reliability of hydrogen fuel cells when applied. [Brief description of the drawings]
[0023] [Figure 1] 1 shows a microstructure sampled after leveling in Example 1. [Diagram 2] This is a microstructure sampled after leveling in Example 2. [Diagram 3] This is a microstructure sampled after leveling in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] In order to clarify the objectives, technical solutions and advantages of the present invention, the present invention will be described in more detail below with reference to the following examples, which are merely for the purpose of illustrating the present invention and are not intended to limit the present invention.
[0025] Example 1: Fabrication of 0.15 mm Hydrogen Fuel Cell Titanium Metal Bipolar Plate Substrate Grade 0 or higher titanium sponge was selected to produce 0.15mm hydrogen fuel cell titanium metal bipolar plate substrate. The titanium sponge was smelted in an EB furnace and machined once, and the Fe content was 0.020%, the C content was 0.010%, the N content was 0.010%, the O content was 0.020%, and the [O] 当A titanium slab with a porosity of 0.062% is obtained, which can be directly used for rolling. The titanium slab raw material is hot-rolled to a thickness of 3.0 mm using a Steckel mill, and the hot-rolled titanium coil in the black skin state is heat-treated and oxide film removed through a continuous annealing shot peening pickling line, where annealing is performed once and shot peening pickling is performed twice. The hot-rolled titanium coil is subjected to multi-step cold rolling and intermediate product annealing using a 20-stage rolling mill and a heat treatment furnace, and a master tape in the annealed state of 0.3 mm is obtained, and the intermediate product annealing temperature is 600°C. Furthermore, the master tape in the annealed state is rolled into a titanium tape of 0.15 mm by a 20-stage rolling mill, and the deformation rate of the rolling process is 50%, and the rolling parameters are as shown in Table 1. The titanium tape is heat-treated to produce the final product by a continuous annealing furnace protected by argon gas. The annealing temperature of the heat treatment is 750°C, the heat retention time is 2min, where the purity of the argon gas is ≥99.99%, and the annealing tension is 2KN. After annealing, the titanium tape is straightened using a tension leveler, the straightening tension is 1000KN, and the tensile deformation rate is 0.20%. After leveling, the sample is sampled, and its microstructure is as shown in Figure 1, and its physical and chemical properties are as shown in Table 2. The final product has excellent physical and chemical properties, good press forming performance, and is pass-proof after pressing, and the waviness of the titanium tape is ≤1.2mm / m, and the thickness precision is ≤±0.002mm. The final product has thickness precision ≤±0.003mm, waviness ≤1.5mm / m, yield strength (R P0.2 )≦260MPa, elongation rate (A 50mm ) ≧ 30%, grain size 6~10, cupping value ≧ 6.0mm.
[0026] Comparative Example 1: A slab was forged by two smelting processes, and the Fe content was 0.040%, the C content was 0.030%, the N content was 0.007%, the O content was 0.070%, and [O] 当A 0.15mm hydrogen fuel cell titanium metal bipolar plate substrate with a pore size of 0.129 was produced, and the other production process and process parameters were the same as those of Example 1. The physical and chemical properties of Comparative Example 1 are shown in Table 2.
[0027] [Table 1]
[0028] [Table 2]
[0029] As can be seen from Table 2, the titanium slab impurity element content of Comparative Example 1 is higher than that of Example 1, so the yield strength, elongation and cupping value of the final product of the titanium metal bipolar plate substrate do not meet the requirements. The final product has high yield strength and low elongation, so the forming performance is relatively poor and the cupping value is low, which results in failure after press forming, and may cause large area cracks after forming.
[0030] Example 2: Fabrication of 0.10 mm Hydrogen Fuel Cell Titanium Metal Bipolar Plate Substrate Grade 0 or higher titanium sponge was selected to produce 0.15mm hydrogen fuel cell titanium metal bipolar plate substrate. The titanium sponge was smelted in an EB furnace and machined once, and the Fe content was 0.037%, the C content was 0.040%, the N content was 0.004%, the O content was 0.050%, and the [O] 当A titanium slab with a porosity of 0.107% is obtained, which can be directly used for rolling. The raw material is hot-rolled to a thickness of 3.0 mm using a Steckel mill, and the hot-rolled titanium coil in the black skin state is heat-treated and oxide film is removed, where annealing is performed once and shot peening pickling is performed twice. The hot-rolled titanium coil is subjected to multi-step cold rolling and intermediate product annealing using a 20-high rolling mill and a heat treatment furnace, and a master tape in the annealed state of 0.2 mm is obtained, and the intermediate product annealing temperature is 750°C. The master tape in the annealed state is rolled to 0.10 mm by a 20-high rolling mill, and the deformation amount of the rolling process is 50%, and the rolling parameter table is as shown in Table 3. The titanium tape is heat-treated to obtain the final product by a continuous annealing furnace under argon gas protection. The annealing temperature of the heat treatment is 700℃, the heat retention time is 1.5min, where the purity of the argon gas is ≧99.99%, and the annealing tension is 2KN. After annealing, the titanium tape is leveled using a tension leveler, the straightening tension is 1500KN, and the tensile deformation rate is 0.30%. After leveling, it is sampled, and its microstructure is as shown in Figure 2, and its physical and chemical properties are as shown in Table 4. The final product has excellent physical and chemical properties, good press forming performance, and is pass after pressing, and the waviness of the titanium tape is ≦1.0mm / m, and the thickness precision is ≦±0.0016mm. The final product has thickness precision ≦±0.003mm, waviness ≦1.5mm / m, yield strength (R P0.2 )≦260MPa, elongation rate (A 50mm ) ≧ 30%, grain size 6~10, cupping value ≧ 6.0mm.
[0031] [Table 3]
[0032] Comparative Example 2: The slab was forged by two smelting processes, and the Fe content was 0.030%, the C content was 0.030%, the N content was 0.012%, the O content was 0.04%, and [O] 当A 0.10 mm hydrogen fuel cell titanium metal bipolar plate substrate with a molecular weight of 0.106 was produced, and rolled to 0.10 mm by a 20-stage rolling mill. The final product was annealed by vacuum cover annealing, and the temperature was kept at 630°C for 2 hours. The physical and chemical properties of Comparative Example 2 are shown in Table 4.
[0033] [Table 4]
[0034] As can be seen from Table 4, the titanium slab impurity element content of Comparative Example 2 is higher than that of Example 2. In addition, the conventional low-temperature covered annealing method is used, so the final titanium metal bipolar plate substrate has yield strength, elongation and cupping value that do not meet the requirements. The forming performance is relatively poor, and the press forming process is unacceptable. After forming, large areas of cracks may occur.
[0035] Example 3: Fabrication of 0.075 mm Hydrogen Fuel Cell Titanium Metal Bipolar Plate Substrate Grade 0 or higher titanium sponge was selected to produce 0.15mm hydrogen fuel cell titanium metal bipolar plate substrate. The titanium sponge was smelted in an EB furnace and machined once, and the Fe content was 0.050%, the C content was 0.020%, the N content was 0.004%, the O content was 0.070%, and the [O] 当A titanium slab with a porosity of 0.119% is obtained, which can be directly used for rolling. The raw material is hot-rolled to a thickness of 3.0 mm using a Steckel mill, and the hot-rolled titanium coil in a black skin state is heat-treated and oxide film is removed, where annealing is performed once and shot peening pickling is performed twice. The hot-rolled titanium coil is subjected to multi-step cold rolling and intermediate product annealing using a 20-high rolling mill and a heat treatment furnace, and a master tape in an annealed state of 0.20 mm is obtained, and the intermediate product annealing temperature is 850°C. The 20-high rolling mill is used to roll it to 0.075 mm, where the deformation rate of the rolling process is 62.5%, and the rolling parameter table is as shown in Table 5. The titanium tape is heat-treated to be the final product by a continuous annealing furnace under argon gas protection. The annealing temperature of the heat treatment is 650℃, the heat retention time is 1min, where the argon gas has a purity of ≧99.99%, and the annealing tension is 1KN. After annealing, the titanium tape is leveled using a tension leveler, the straightening tension is 500KN, and the tensile deformation rate is 0.10%. After leveling, it is sampled, and its microstructure is as shown in Figure 3, and its physical and chemical properties are as shown in Table 6. The final product has excellent physical and chemical properties, good press forming performance, and is pass after pressing, and the waviness of the titanium tape is ≦1.0mm / m, and the thickness precision is ≦±0.0012mm. The final product has a thickness precision ≦±0.003mm, waviness ≦1.5mm / m, yield strength (R P0.2 )≦260MPa, elongation rate (A 50mm ) ≧ 30%, grain size 6~10, cupping value ≧ 6.0mm.
[0036] [Table 5]
[0037] Comparative Example 3: The slab was forged by two smelting processes, and the Fe content was 0.050%, the C content was 0.020%, the N content was 0.004%, the O content was 0.098%, and [O] 当A 0.075mm hydrogen fuel cell titanium metal bipolar plate substrate with a pore size of 0.147 was produced, and the hot-rolled titanium coil was subjected to multi-step cold rolling and intermediate product annealing using a 20-high rolling mill and a heat treatment furnace to obtain a master tape in an annealed state of 0.50mm, which was then rolled to 0.075mm by a 20-high rolling mill. The deformation rate of the final product in the rolling process was 85%, and no straightening was performed after annealing. The physical and chemical properties of Comparative Example 3 are shown in Table 6.
[0038] [Table 6]
[0039] As can be seen from Table 6, the titanium slab impurity element content of Comparative Example 3 is higher than that of Example 3, and the deformation amount of the final product during the rolling process is larger. Therefore, the final product of the titanium metal bipolar plate substrate does not meet the requirements in yield strength, elongation and cupping value, and the forming performance is relatively low. After press forming, it is rejected, and after forming, large area cracks may occur.
[0040] As should be understood, the above embodiments are only for illustrating the present invention, and the present invention is not limited to the above embodiments. According to the technical essence of the present invention, simple modifications, equivalent changes and modifications to the above embodiments are all within the protection scope of the present invention.
Claims
1. 1. A method for manufacturing a hydrogen fuel cell titanium metal bipolar plate substrate, comprising: (1) A process for obtaining a titanium slab by smelting and machining a titanium sponge, comprising: 当 is defined as the mass ratio of the total content of impurity elements in the titanium slab, the mass ratios of the contents of Fe, C, N, and O impurity elements are defined as [Fe]%, [C]%, [N]%, and [O]%, respectively, and [O] 当 The formula is: [O] 当 = [O]% + 0.5 * [Fe]% + 0.7 * [C]% + 2.5 * [N]%, [Fe]%≦0.050%, [C]%≦0.040%, [N]%≦0.010%, [O]%≦0.080%, [O] 当 selecting a titanium slab having a titanium content of ≦0.120% for direct rolling; (2) hot rolling the titanium slab selected in step (1) to obtain a hot rolled titanium coil in a black skin state, and then surface treating the titanium coil to obtain a hot rolled titanium coil having no oxide film or defects remaining on the surface; (3) subjecting the hot-rolled titanium coil obtained in step (2) to multiple cold rolling steps and intermediate product annealing to obtain a master tape for rolling the final product; (4) rolling the master tape for final product obtained in step (3) into a final product to obtain a titanium tape; (5) carrying out a final product heat treatment and straightening of the titanium tape obtained in step (4) by continuous annealing under the protection of argon gas to obtain the hydrogen fuel cell titanium metal bipolar plate substrate; Including, In step (5), the heat treatment temperature of the continuous annealing is 600-800°C, the heat retention time is 0.5-2.5min, the annealing tension is 0.5-2.5KN, and the purity of the argon gas is ≧99.99%.
2. 2. The method for manufacturing a titanium metal bipolar plate substrate for hydrogen fuel cells according to claim 1, characterized in that in step (1), the titanium sponge is a titanium sponge of grade 0 or higher.
3. 2. The method for manufacturing a titanium metal bipolar plate substrate for hydrogen fuel cells according to claim 1, characterized in that in step (1), the smelting is carried out once by an EB furnace.
4. The manufacturing method of titanium metal bipolar plate substrate for hydrogen fuel cell according to claim 1, characterized in that in step (2), the surface treatment process is to carry out annealing once and shot peening pickling twice on the hot rolled titanium coil in black skin state by a continuous annealing shot peening pickling line, and then carry out polishing and shot peening pickling treatment.
5. The method for manufacturing hydrogen fuel cell titanium metal bipolar plate substrate as claimed in claim 1, characterized in that in step (3), the temperature of intermediate product annealing is 600-850°C.
6. In step (4), the deformation amount in the rolling process is 50% to 65%, and the unit tension is 200 to 400 kg / mm 2 The method for manufacturing hydrogen fuel cell titanium metal bipolar plate substrate as claimed in claim 1, characterized in that, the rolling speed is 50-150m / min, and the rolling force is 200-400t.
7. The manufacturing method of titanium metal bipolar plate substrate for hydrogen fuel cell according to claim 1, characterized in that in step (5), the tension of straightening is 500-1500KN, and the tensile deformation rate of straightening is 0.1%-0.3%.
8. The hydrogen fuel cell titanium metal bipolar plate substrate obtained in step (5) has a thickness precision of ≦±0.003 mm, a waviness of ≦1.5 mm / m, and a yield strength (R P0.2 )≦260MPa, and elongation (A 50mm 2. The method for manufacturing hydrogen fuel cell titanium metal bipolar plate substrate according to claim 1, characterized in that: 1.)≧30%, 2.) grain size is 6-10, and 3.) cupping value is ≧6.0 mm.
Citation Information
Patent Citations
Processing method of low yield ratio high strength titanium coiled plate for heat exchanger
CN103409642A
Processing method for high-purity titanium sheet for coating titanium anode base material
CN105170686A
Roll type production method of titanium and palladium alloy
CN105886983A
Process method for increasing material yield of cold-rolled titanium strip coil
CN112122340A
Preparation process method of wide ultrathin cold-rolled titanium strip coil for rolling bonding
CN112122382A